Chapter The Influence of Candida spp. in Intestinal Microbiota; Diet Therapy, the Emerging Conditions Related to Candida in Athletes and Elderly People - Schwarze, Ann-Kristin (InTechOpen, 2020)
The presence of Candida in the gut is normal, but an overproduction may lead to serious health problems due to an imbalanced gut, causing gut-related symptoms such as bowel movement changes, excessive gas, etc. Some diseases, such as Crohn's disease and ulcerative colitis, are associated with an overgrowth of Candida in the gastrointestinal tract. Several recent studies have shown that a prolonged candidiasis within the intestines is associated with Candida overgrowth syndrome or chronic fatigue syndrome. A healthy digestive system relies on a good balance of bacteria that live in the gut, and an important role in maintaining this balance is having the ingested type of food. Candida overgrowth can be prevented first of all by healthy eating patterns, as susceptibility is increased by a high-sugar diet and diabetes or nutritional deficiencies causing a dysregulated immune system. In general, Candida-associated conditions have a high impact on performance. Recent research has shown an increasing interest in the Candida-related conditions and diseases.